“O segredo de uma família feliz”: representações sobre família entre as Testemunhas de Jeová em Santo Estevão/Ba (1970-2001) - Bastos, Camila Noêmia Rener Santos (2014)
The present study analyzes the representations of family among Jehovah's Witnesses in the city of St. Stephen, Bahia, located between the hinterland and Recôncavo, 40 km from Feira de Santana, from 1970 to 2001. The time frame of the research is related the beginning of the proselytizing activities of the group and ends with the construction of Kingdom Hall Avenue Teixeira de Freitas, one of the main avenues of the city. The study aimed to examine the tensions and power struggles in the holy - estevense religious field , caused by the insertion of a new group , especially for the strong influence of Catholicism in society of this city. The main tenets of the group , the millenarian character, identity building of the faithful and a new world view guided on the ideas of Jehovah's Witnesses are also discussed in this dissertation. We also analyzed the present among Jehovah's Witnesses , Bible -centered , with well-defined gender roles and differences that manifest in the ecclesiastical hierarchy of the group androcentric discourse, since women do not hold jobs, despite the strong performance of proselytism and in the same Hall of internal activities, such as attending meetings, cleaning, among others. In the family, gender inequalities are also present, because the man is the head of the family, " head " and the woman, her helper, submissive to him. This is the model family that Jehovah's Witnesses are intended to represented by them, which involves the construction of habitus. However, between discourse and practice are the experiences and experiences of individuals who appropriate this discourse.